2020
DOI: 10.1016/s2214-109x(19)30458-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between interpregnancy interval and subsequent stillbirth in 58 low-income and middle-income countries: a retrospective analysis using Demographic and Health Surveys

Abstract: Background About 3 million stillbirths occur each year, 98% of which are in low-income and middle-income countries (LMICs). Interpregnancy interval is a key risk factor of interest, because it is modifiable. We aimed to investigate whether there is a causal relationship between the length of interpregnancy interval and risk of subsequent stillbirth. MethodsWe used Demographic and Health Surveys (2002-18) from 58 LMICs to study reproductive histories of women and to identify livebirths and stillbirths in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
0
28
2
Order By: Relevance
“…We argue that just like miscarriages, stillbirths are also natural events and women who experience stillbirth may have been exposed to risk factors such as stress from their partners, families or struggling to meet routine deadlines at work as established in the literature [33][34][35] and these stressful events are more likely to occur in marriages. In relation to our finding that the odds of stillbirth is lower among women with higher parity, it contradicts the findings of studies that have identified that high chances of stillbirth characterise women with multiple pregnancies [39][40][41] and those that have found a u-shaped relationship between parity and stillbirths [42,43]. Notwithstanding, the possible reason for our finding could be explained in terms of pregnancy experience obtained by women with higher parity which could empower them to observe essential health practices that protect them from stillbirths.…”
Section: Discussioncontrasting
confidence: 99%
“…We argue that just like miscarriages, stillbirths are also natural events and women who experience stillbirth may have been exposed to risk factors such as stress from their partners, families or struggling to meet routine deadlines at work as established in the literature [33][34][35] and these stressful events are more likely to occur in marriages. In relation to our finding that the odds of stillbirth is lower among women with higher parity, it contradicts the findings of studies that have identified that high chances of stillbirth characterise women with multiple pregnancies [39][40][41] and those that have found a u-shaped relationship between parity and stillbirths [42,43]. Notwithstanding, the possible reason for our finding could be explained in terms of pregnancy experience obtained by women with higher parity which could empower them to observe essential health practices that protect them from stillbirths.…”
Section: Discussioncontrasting
confidence: 99%
“…They do not have the ability to live independently, and they are not physically or psychologically ready for pregnancy. Premature pregnancy has adverse effects on health 1,2,[6][7][8]10,11,19,22,[28][29][30] . Our study demonstrated that higher risks of eclampsia, severe anaemia, and MNM were observed at a gestational age greater than 37 weeks among adolescent mothers compared with mothers aged 20-24 years.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal outcomes were restricted to live births at 28 gestational weeks or later or to a birthweight of more than 1000 grams, in accordance with the de nition of third-trimester stillbirth from the WHO 19 . Gestational age in China is generally ascertained on the basis of the last menstrual period or the ultrasound examination when the date of the last menstrual period is not known 20 .…”
Section: De Nitionmentioning
confidence: 99%
“…We defined the IPI as the time between the end of one pregnancy and the start of the next pregnancy (Swaminathan et al ., 2020). This was established by reviewing the AHRI pregnancy registry and calculating the time in months between the date that the first pregnancy ended and the date of the last menses associated with the start of the second pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Given these implications, and the projected exponential growth of the SSA population in the next few decades (Ezeh et al ., 2020), interest in understanding modifiable risk factors for pregnancy loss in this region has gained momentum. The interpregnancy interval (IPI), or the period of time between the end of one pregnancy and the start of the next pregnancy (Swaminathan et al ., 2020), is perhaps one of the least understood modifiable risk factors for pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%